2012
DOI: 10.1007/s13361-012-0462-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of Probe Electrospray Ionization Mass Spectrometry (PESI-MS) to Clinical Diagnosis: Solvent Effect on Lipid Analysis

Abstract: We have examined several combinations of solvents with the aim of optimizing the ionization conditions for molecular diagnosis of malignant tumours by PESI-MS. Although the best conditions may depend on the actual species in the sample, the optimal conditions for renal cell carcinoma (RCC) were achieved by using alcohols. PESI-MS successfully delineated the differential expression of phospholipids (PCs) and triacylglycerols (TAGs) in noncancerous and RCC tissues by using these solvent systems. This study paves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…MRM analysis revealed a4 0% decrease in signal intensity when compared with the results from an open emitter ( Figure S4). TherESI phenomenon occurs with all the types of emitters tested, including capillaries of borosilicate,q uartz, or fused silica, steel needles, [12] thetashaped capillaries, [13] and those made of porous materials like wooden tips [14] and paper. by sputter-coating al ayer of Pd/Au; Figure S3).…”
Section: Methodsmentioning
confidence: 99%
“…MRM analysis revealed a4 0% decrease in signal intensity when compared with the results from an open emitter ( Figure S4). TherESI phenomenon occurs with all the types of emitters tested, including capillaries of borosilicate,q uartz, or fused silica, steel needles, [12] thetashaped capillaries, [13] and those made of porous materials like wooden tips [14] and paper. by sputter-coating al ayer of Pd/Au; Figure S3).…”
Section: Methodsmentioning
confidence: 99%
“…Later, Hiraoka et al reported a technique called probe electrospray ionization (PESI), 36) which uses a stainless steel needle with micrometer-sized tip as the ESI emitter. PESI has been demonstrated to be useful in applications, such as clinical diagnosis, 37) detection of illicit drugs in body uids, 38) reaction monitoring, 39) and analysis of biological samples. 40) Solvent droplets over a solid metal substrate with high voltage undergo a process similar to in traditional electrospray, in which a metal-made hollow capillary is used to direct sample solution and as the ESI emitter.…”
Section: Esi Emitter Solid Metal Substratesmentioning
confidence: 99%
“…A new ionization method, probe electrospray ionization (PESI)–mass spectrometry (MS), which uses a solid needle as a sample probe and an ESI emitter, was developed by Hiraoka et al and can be applied not only to liquid and surface analyses, but also to the inside of samples. As PESI usually requires no pretreatment steps, PESI–MS has been used in several fields, such as food science, plant science, studies of chemical reaction mechanisms, medical and clinical diagnosis, and metabolomics . In this study, we used PESI–MS/MS for the direct detection of MT‐45, an opioid analgesic psychoactive substance, in human tissues in an actual forensic case.…”
Section: Introductionmentioning
confidence: 99%